2010
DOI: 10.1159/000313698
|View full text |Cite|
|
Sign up to set email alerts
|

Does Guideline-Adherent Therapy Improve the Outcome for Early-Onset Breast Cancer Patients?

Abstract: Background and Objective: Guidelines for the treatment of early-onset breast cancer have been proposed in several countries, but to date, their impact on outcomes is unverified. The objective of this study was to evaluate the association between guideline-adherent versus nonadherent treatment and recurrence-free survival (RFS) and overall survival (OAS) in early-onset breast cancer patients. Methods: A total of 1,778 patients were included in the study, of whom 111 were 35 years or younger and 1,667 were betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 18 publications
1
32
0
4
Order By: Relevance
“…No significant differences in total or surgical subscores were observed between patients operated by surgeons in the intermediate (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences in total or surgical subscores were observed between patients operated by surgeons in the intermediate (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) …”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of both patients and health care providers [8] have been related to these variations. Hospital and physician volume [9], specialization [10,11], participation in research [9], multidisciplinary teams [12] and treatment in accordance to guidelines [13] have been found to affect both the way patients are cared for and the outcomes. Variations in treatment include type of breast and axillary surgery, and use of chemotherapy, hormone therapy and radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…About every 10th woman diagnosed with BC in Germany is younger than 45 years [1]. Younger women are often affected by a more aggressive form of this disease [2,3]. When treating this young population, special factors have to be taken into consideration: long recurrence-free survival (RS) and overall survival (OS) have to be weighed against quality of life and reintegration into family and work life.…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the article by Varga et al recently published in Oncology [1]. Using data of 1,778 patients with early onset breast cancer (55 years or younger), the authors reported that guideline adherence to surgical treatment, radiotherapy, anti-estrogen/endocrine therapy and chemotherapy significantly improved overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…As in the study of Varga et al [1], information on the operationalization of ‘guideline adherence’ is sparse, it is difficult to assess to which magnitude the above-mentioned methodological issues may have biased the results. Other publications that used the same database to address the influence of guideline adherence on mortality did not provide substantially more information on the methods used [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%